2018
DOI: 10.17058/tecnolog.v22i2.12125
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho operacional e energético de um trator agrícola durante operação de gradagem

Abstract: Este trabalho teve por objetivo avaliar a capacidade de campo efetiva e o consumo operacional de combustível de um trator agrícola, utilizando diferentes tamanhos de grades niveladoras e velocidades de trabalho, durante a operação de gradagem. O experimento foi conduzido sobre solo classificado como Argissolo Vermelho distrófico arênico, com delineamento experimental em blocos ao acaso e três repetições, totalizando 27 unidades experimentais. Utilizaram-se três grades niveladoras leves de 28, 32 e 36 discos ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
1
1
0
2
Order By: Relevance
“…The F C had a lower result for the harvest in a single line, which even with a higher V O , had a smaller working width, reflecting the lower average of F C between harvesting modalities (Table V). A similar result was found by Farias et al (2018), who, when evaluating different implements for soil preparation, concluded that the increase in working width allows reaching larger areas worked in the same period, compensating for differences in travel speeds. Among the modalities of total area harvesting, the one that had support (T TAS ) showed a F C 22% higher than the other (Table V), because of the faster travel speed and the greater efficiency obtained in the operation due to the use of the transshipment set, and as a consequence, the harvest interruption time was shorter.…”
Section: Analysis E R (Rpm)supporting
confidence: 80%
“…The F C had a lower result for the harvest in a single line, which even with a higher V O , had a smaller working width, reflecting the lower average of F C between harvesting modalities (Table V). A similar result was found by Farias et al (2018), who, when evaluating different implements for soil preparation, concluded that the increase in working width allows reaching larger areas worked in the same period, compensating for differences in travel speeds. Among the modalities of total area harvesting, the one that had support (T TAS ) showed a F C 22% higher than the other (Table V), because of the faster travel speed and the greater efficiency obtained in the operation due to the use of the transshipment set, and as a consequence, the harvest interruption time was shorter.…”
Section: Analysis E R (Rpm)supporting
confidence: 80%
“…A grade destorroadora apresentou valor satisfatório, influenciado pela velocidade ter se aproximado bastante da Norma. Farias et al (2018) avaliando o desempenho operacional e energético de um trator agrícola durante operação de gradagem, com uma grade niveladora de 2,34 m de largura na velocidade de 6,7 km h -1 , obtiveram valor de Capacidade de Campo (Operacional) Efetiva de 1,13 ha h -1 , valor este muito próximo do encontrado neste trabalho. Mesmo utilizando uma velocidade abaixo dos autores citados, ou seja, de 6 km h -1 , encontrou-se, neste caso, o valor de 1,15 ha h -1 , demonstrando alta produtividade e aproveitamento do trabalho efetuado.…”
Section: Figura 1 -Eficiência Dos Equipamentos Utilizadosunclassified
“…A competitividade imposta ao setor produtivo brasileiro faz com que o agricultor busque alternativas para aumentar a produtividade sem aumentar os custos de produção [1]. Neste sentido, tem-se dado maior atenção para a qualidade de semeadura para a cultura do milho [2].…”
Section: ____________________________________________________________________________________________________________ 1 Introduçãounclassified